Alphaherpesvirus DNA replication in dissociated human trigeminal ganglia - Cohrs, Randall J. (J Neurovirol, 2016)
Analysis of the frequency and PCR-quantifiable abundance of herpes simplex virus type 1 (HSV-1) and varicella zoster virus (VZV) DNA in multiple biological replicates of cells from dissociated, randomly distributed human trigeminal ganglia (TG) of 4 subjects revealed an increase in both parameters and in both viruses during 5 days of culture, with no further change by 10 days. Dissociated TG provides a platform to analyze initiation of latent virus DNA replication within 5 days of culture.